2020
DOI: 10.1111/grs.12284
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value, fermentation profile and effluent loss in sweet potato vine silage, with or without microbial inoculant

Abstract: The nutritive value, fermentation profile, microbial population, and effluent and gases losses of sweet potato vine silages, with and without microbial inoculant, were evaluated. The experiment was conducted in a 5 × 2 factorial arrangement, with five sweet potato genotypes (BD‐08, BD‐23, BD‐25, BD‐31TO and BD‐43) and presence/absence of microbial inoculant (Sil‐All® 4 × 4), in a randomized blocks design, with three replicates. After 48 hr of wilting in field, the vines were chopped, inoculated with microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(46 reference statements)
0
1
1
Order By: Relevance
“…However, we can observe in this work that the lignin content in the fresh sweet potato branches was 9.79%; after ensiling, due to the fermentation process that took place, this value decreased to 7.64% at 45 days and 7.33% at 120 days, without significant differences being observed. These values were lower than those found by Pereira et al (2021b), who found lignin levels greater than 13% for sweet potato silage from vines. The observed differences may be related to the maturation stage of the sweet potato harvest.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…However, we can observe in this work that the lignin content in the fresh sweet potato branches was 9.79%; after ensiling, due to the fermentation process that took place, this value decreased to 7.64% at 45 days and 7.33% at 120 days, without significant differences being observed. These values were lower than those found by Pereira et al (2021b), who found lignin levels greater than 13% for sweet potato silage from vines. The observed differences may be related to the maturation stage of the sweet potato harvest.…”
Section: Resultscontrasting
confidence: 78%
“…because some microbial processes can still occur due to bacteria that remain active for long periods and thus compromise the quality and viability of sweet potato vine silage (Pereira 2021b). Information on the quality of sweet potato vine silage available in the literature is still scarce.…”
Section: Introductionmentioning
confidence: 99%